WTO dispute settlement procedure: Implications for a small country - Chris Nixon (New Zealand Institute of Economic Research (NZIER), 2002)
[Introduction] What is international trade? Amongst the rhetoric in the media coverage of the World Trade Organisation (WTO), it is often forgotten that it is businesses not governments that, to a large extent, engage and drive world trade. It is businesses who identify opportunities in other regions and international trade is simply an aggregation of the fruits of those transactions on a national basis. For example, if a firm in Wellington sees an opportunity in Auckland, no one pays any attention. If the same firm sees an opportunity in another country to sell an identical good - politicians and other interested parties feel they have a right to comment on, become involved in, or even try to stop the transaction.
Keywords: 330; Internationale Schiedsgerichtsbarkeit; WTO-Regeln; Kleines-Land-Modell